Socio-Economic Sistemology: Multidimensional Science for a Comprehensive Study of the Socio-Economic and Legal System - Shokhmansur, Shokhazamiy; ., Elmuradov D. (Journal of Economics and Behavioral Studies, 2014)
The main feature of the development of science in the second half of the 20th century was the transition from a single-dimensional science of past centuries, based mainly on experimentation, to the science of two dimensional, which is based on a systems approach. However, the conditions and trends of development of the world economy and society, therefore, the humanities and social sciences, including economics, in the twenty-first century calls for transition to new more advanced phase of science to integrated presentation and study in the relationship between the various components of the socio-economic and legal systems (SELS) based on a systematic approach. The importance of this completely new paradigm of science-its transition from two dimension in the multi dimension in general socio-economic and legal space is already quite fully understood, because it is based a well elaborated the theoretical-methodological and practical implications for the future of the base, a it seems extremely profound and promising.